Evolution of Precision Medicine and Surgical Strategies for Bicuspid Aortic Valve-Associated Aortopathy - Fatehi Hassanabad, Ali; Barker, Alex J.; Guzzardi, David; Markl, Michael; Malaisrie, Chris; McCarthy, Patrick M.; Fedak, Paul W. M. (Frontiers in Physiology, 2017)
Bicuspid aortic valve (BAV) is a common congenital cardiac malformation affecting 1-2% of people. BAV results from fusion of two adjacent aortic valve cusps, and is associated with dilatation of the aorta, known as bicuspid valve associated aortopathy. Bicuspid valve aortopathy is progressive and associated with catastrophic clinical events, such as aortic dissection and rupture. Therefore, frequent monitoring and early intervention with prophylactic surgical resection of the proximal aorta is often recommended. However, the specific pattern of aortopathy is highly variable among patients, with different segments of the ascending aorta being affected. Individual patient risks are sometimes difficult to predict. Resection strategies are informed by current surgical guidelines which are primarily based on aortic size and growth criteria. These criteria may not optimally reflect the risk of important aortic events. To address these issues in the care of patients with bicuspid valve aortopathy, our translational research group has focused on validating use of novel imaging techniques to establish non-invasive hemodynamic biomarkers for risk-stratifying BAV patients. In this article, we review recent efforts, successes, and ongoing challenges in the development of more precise and individualized surgical approaches for patients with bicuspid aortic valves and associated aortic disease.